Dysphagia and dysarthria: unusual presentation of Myasthenia Gravis. - Ferreira, Sara (2008)
Myasthenia Gravis is an autoimmune disorder that generally presents with ocular symptoms, specially diplopia and ptosis. Dysphagia may be a manifestation of the generalised type of the disease, but rarely is its presenting feature. The authors describe a case of Myasthenia Gravis in an old patient complaining of dysphagia and dysarthria. Because Myasthenia Gravis is a potentially serious but treatable disease, we emphasize the need to consider it in the differential diagnosis of dysphagia, namely in the elderly. In fact, the disorder is probably underdiagnosed in this population group, because clinicians tend to accept other more frequent diagnosis to explain these symptoms.